A Comparative Analysis of Three Screening Methods for Nonsuicidal Self‐Injury in College Students. Issue 3 (8th October 2018) - Lund, Emily M.; Thomas, Katie B.; Nadorff, Danielle R.; Bouchard, Lauren M.; Galbraith, Kate; Bradley, April R.
Abstract : This study compared college students' ( N = 260) responses on a simple dichotomous screening measure and 2 behavior checklists. Seventy‐nine participants (30.4%) screened positive (i.e., endorsed nonsuicidal self‐injury [NSSI] behavior) on at least 1 measure, and 37 (46.8%) screened positive on the simple screen. Participants who screened positive on the simple screen reported more forms and instances of NSSI than did those who screened positive only on the checklist measures. They also reported significantly greater psychological distress compared with all other participant groups.